212k views
1 vote
(64 Points) 2y+3=-1(x-2) in standard form

1 Answer

4 votes

Explanation:

First, standard form is

a

x

+

b

y

+

c

=

0

In this question, we can expend the formula and rearrange it.

You can try it first, and the steps are as follow:

Step 1: Expend it

2

y

+

3

=

1

3

x

+

2

3

As there are fraction in the formula and it doesn't look good, we can eliminate it by multiplyng 3.

Step 2: Multiply by 3

6

y

+

9

=

1

x

+

2

Step 3: Rearrange the terms

x

+

6

y

+

7

=

0

User Peter Becker
by
4.7k points